DESIGN AND IMPLEMENTATION SQUARE PATCH MICROSTRIP ANTENNA AT FREQUENCY 2.3 GHz - Dimas Mahesa Muharom; Erma Triawati CH (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2019)
Abstract— In this research has been done the design and implementation of microstrip antenna for WiMAX application working on a frequency of 2.3 GHz, with the size of 5 x 5 cm and generate the appropriate parameter regulation WiMAX Dirjenpostel [1]. The method used i.e. square patch, proximity coupled feeding and modified slot on the antenna ground. Its design stages, namely to determine the initial size of the antenna, simulation, and optimization. Occurs the difference measurement results and simulations that are caused by factors of fabrication and measurement methods are not ideal. The difference in those results i.e. increase the gain of 6.8634 dB or increased 363.79% (simulated results 1.8866 dB, measurement results 8.75 dB), decrease the bandwidth of 36 MHz (from 131 MHz be 95 MHz). For differences in the VSWR of 0.1258 and the input impedance of 3,666 Ω it can still be tolerated and the radiation pattern produced is identical. Index Terms—Microstrip Antenna, Square Patch, Proximity Coupled, Modified Slot. DOI : https://doi.org/10.26905/jeemecs.v2i1.2744